Application of Edible Coating from Konjac Flour added with Chitosan on the Quality of Red Chili - Rusdianto, Andrew Setiawan; Hidayah, Ridatul Winda; Amilia, Winda (Department of Agroindustrial Technology, Faculty of Agricultural Technology UGM, 2024)
Red chilies have a relatively short shelf life and are highly perishable. Red chili is one type of vegetable with a water content (60 - 90 %) at the time of harvest and an increase in respiration rate. Therefore, it is necessary to pack a coating that can reduce and suppress respiration and transpiration rates to prevent vegetable damage. One potential way to reduce the damage to red chilies is by applying edible coatings. Edible coating is one technique that can be developed and applied to maintain quality and extend the shelf life of red chili. This study aims to determine the quality characteristics of red chili (Capsicum annuum L) before and after coating edible coating. In addition, to analyze the effect of Konjac flour concentration on the quality characteristics of red chili (Capsicum annuum L) with the addition of chitosan and to find out the best treatment for the application of edible coating with the basic ingredients of Konjac flour with the addition of chitosan. This study used a completely randomized design (CRD) and three replications. The treatment in this study was the storage time of coated red chilies edible coating for 1, 3, 6, and 9 days. The results showed that the storage time of coated red chilies edible coating affects the pH, water content, weight loss, respiration rate, and color. The analysis of the characteristics of red chilies showed that the coating done on red chilies can reduce and suppress the process of respiration rate.